Morphometric Attributes of Two Native Forage Species According to Water Source Distance in Semiarid Central Grasslands of Argentina - Suárez, Carla Etel (2024)
The semiarid grasslands of Argentina’s central region have been modified by domestic livestock grazing, both in their composition and structure. The increase in the proportion of woody and non-forage species and the decrease in forage species are some of the most evident results of this process. There is limited available information about the effect of differential grazing pressures on morphometric attributes of native species, and it also depends on the life histories of the species in this grassland. The objective of this work was to evaluate some morphometric aspects in the grasses Poa ligularis Nees ex Steud and Piptochaetium napostaense (Speg.). Hack according to distance from the water source in communities in the central semiarid region of Argentina. The study area included areas of low grassland, golden forests, and secondary forests in grasslands (6 fields with 9 paddocks). Grazing pressure was established based on the distance to the water source, so sampling areas were designated near the water source (grazing pressure is greater) and far from the water source (grazing pressure light) in each of the pastures. In both species, specimens were selected at random, and the following attributes were measured: crown diameter at ground level (cm), burial depth (cm), average tiller weight per plant (g. Marcello−1), and the density of tillers per unit of crown surface (tillers.cm−2 crown). The morphometric attributes evaluated showed differences according to the distance to the watering hole and in the different pastures. Both species presented similar behaviors for the attributes. There were significant differences in the depth of burial and the average weight of tillers per plant, being greater in the areas close to the water source. Regarding the distance to the watering hole, there were no significant differences in crown diameter and tiller density, but the highest values were recorded for the former near the watering hole and for the second far from the watering hole. In pastures with low grassland or secondary forest on the plain, the greatest depth of burial and weight of tillers was recorded closer to the water. In forest areas, the highest density of tillers was found far from the water. For crown diameter, although there was no interaction, the largest diameters were found in plain grassland areas near the waterhole. In general, both species had a differential behavior depending on the grazing pressure that was evident along the physiognomic gradient from plain grassland to forest and that could be interpreted as a strategy to perpetuate themselves against herbivory.